Solventes bio-renováveis para metátese de propenilbenzenos - Pedro Leroy Evangelista Carvalhais (2019)
Metathesis reactions have emerged in the last few decades as important tools for a wide variety of organic synthesis, combining high yields and sustainability. In spite of intense studies in this area and developments optimizing metathesis conditions, in many cases solvent utilization is mandatory, especially in fine chemistry. The most widely employed classes of solvents are aromatics and chlorinated ones, suchas toluene and 1,2 -dichloroethane, that are rather toxic and harmful to the environment, which compromises the sustainable utilization of olefin metathesis. In this study, the substitution of those traditional and environmentally problematic solvents for biodegradable and less aggressive options was evaluated. The chosen test reactions were: ring closing metathesis of diethylallylmalonate and cross metathesis of anethole and methylacrylate. Anisole, e pinenes, pinane, limoneneand a mixture of pinane and p-cymene were employed for the first time for this reaction. High yields were achieved, specially with anisole and the mixture pcymene/pinane, showing that they can replace harmful traditional solvents.